2020
DOI: 10.29244/jtcs.7.01.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sago Land Utilization by Intercropping with Eggplants, A Study at Tanjung Peranap Village, Meranti Island, Riau, Indonesia

Abstract: Sago palms are the main food crops in eastern part  of Indonesia. Sago productivity can reach 20 to 40 per ha per year, and the trees can be harvested when they are 10 years of age. Due to long duration before harvesting it is important that sago growers could grow annual food crops. The objective of study is to determine the growth of sago palm intercropped with eggplants, and how intercropping aff ects each crop grown as monoculture. The study was carried out from March to July 2018 at Tanjung Peranap Villag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of [28], [29], [30], [31], and [32] indicate that several factors influence repeated purchases on the OVO digital wallet application, including service, ease of use, and consumer satisfaction. [32], [33], [34], and [35] found a relationship between service quality and customer satisfaction, and word-of-mouth behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of [28], [29], [30], [31], and [32] indicate that several factors influence repeated purchases on the OVO digital wallet application, including service, ease of use, and consumer satisfaction. [32], [33], [34], and [35] found a relationship between service quality and customer satisfaction, and word-of-mouth behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This research is supported by [29], which found that OVO application user satisfaction, as a result of the ease of use, significantly influences the repurchase of the OVO application. Research from [30] states that several factors influence repurchasing on the OVO application, namely service quality, ease of use, and satisfaction of OVO users. [31] proposed the influence of service quality on repurchase and showed that eservice quality significantly affects customer satisfaction and loyalty to the OVO application.…”
Section: F Effect Of Ovo User Consumer Satisfaction Variables On Repe...mentioning
confidence: 99%
“…The sago one of Indonesia's wealth, because of the total area of sago forest in the world, Indonesia has one million hectares of sago forest spread over several provinces or controls 51.3% of the world's sago forest. The largest sago palm area in Indonesia is found in several areas, namely Papua, Maluku, Riau and Central Sulawesi [1]. Starch is a homopolysaccharide consisting of glucose units linked together by glycosidic bond.…”
Section: Introductionmentioning
confidence: 99%